Automated calibration of model-driven reconstructions in atom probe tomography. (15th September 2022) - Fletcher, Charles; Moody, Michael P; Fleischmann, Claudia; Dialameh, Masoud; Porret, Clement; Geiser, Brian; Haley, Daniel
Abstract: Traditional reconstruction protocols in atom probe tomography frequently feature image distortions for multiphase materials, due to inaccurate geometric assumptions regarding specimen evolution. In this work, the authors' outline a new reconstruction protocol capable of correcting for many of these distortions. This new method uses predictions from a previously developed physical model for specimen field evaporation. The application of this new model-driven approach to both an experimental semiconductor multilayer system and a fin field-effect transistor device (finFET) is considered. In both systems, a significant reduction in multiphase image distortions when using this new algorithm is clearly demonstrated. By being able to quantitatively compare model predictions with experiment, such a method could also be applied to testing and validating new developments in field evaporation theory.